Towards an Understanding of Hop Tolerance in Beer Spoiling Lactobacillus brevis - Vogel, Rudi F.; Behr, Jürgen; Preissler, Patrick (BrewingScience, 2010)
Lactobacillus brevis comprises strains with diverse metabolic capabilities. Some specialized strains can grow even in highly hopped pilsner beers without the need of long term adaptation. Other strains develop tolerance upon prolonged hop exposition or remain sensitive. In this communication genetic analyses, proteomics and physiological tests in beer as well as studies in membrane physiology and cell wall composition are reviewed, which are useful to differentiate L. brevis strains along their beer spoiling potential and to elucidate decisive marker traits for categorizing beer spoiling L. brevis along their relevance for the brewer. Hop adaptation in L. brevis TMW 1.465 is a multifactorial process, which results in changes in metabolism, protein profile, membrane and cell wall composition and intracellular manganese levels. It involves mechanisms to cope with intracellular acidification and divalent cation limitation, redox imbalance and oxidative damage and mechanisms for energy generation and economy, genetic information fidelity and enzyme functionality, and as a result enables beer spoilage. Differentiation along the beer spoiling capacity is possible by comparative proteomics, or by physiological tests employing manganese efflux or reduction of tetrazolium to formazan upon growth in lager beer. A simple test for mangenese efflux provides a useful tool for categorization of beer spoiling L. brevis. On the other hand, genetic determinants potentially useful for PCR detection systems were widely spread in all strains with no reference to high hop tolerance. The further understanding of hop tolerance requires comparative genomic studies revealing critical strain differences and thus multiple (PCR) markers.